Determinants of E- recruitment adoption in Nigerian civil service: attitude as a moderator - Tangaza, Ibrahim Aminu author (School of Business Innovation & Technopreneurship, 2017)
The study focuses on the determinants of e-recruitment adoption with the potentially of user attitude as a moderator in the Nigerian civil service. It covers ministries and local government areas in three state of North Western Nigeria, (e.g Sokoto, Kebbi and Zamfara states). The ministries and local governments comprise the total number of 112 population, and individual as the unit of analysis of this study, where 2 respondents representing each organization (Head of human resource department and staff officers). These respondents are expected to represent the sampled ministries and local governments (i.e. unit of analysis) objectively by each completing a structured questionnaire distributed using proportionate random sampling techniques.